Women Migrants Today: New Directions, No Papers, Old Barriers. Issue 3 (September 2014) - Bloch, Alice; Kumarappan, Leena; McKay, Sonia
<x xml:space="preserve">Abstract</x> The article explores the changing nature of female migration, showing how the composition of the migrant population has altered, with women migrants now comprising a majority of the recent migrant populations. Drawing on data from interviews with undocumented migrant women in London, the article looks at the consequence of undocumented status for women, explores how they look for work, their jobs, pay, and terms and conditions, how they express their relationships within the workplace, what they identify as the supportive characteristics of coworkers, and how they manage when not in work.